Web-Age Information Management WAIM 2014 International Workshops: BigEM, HardBD, DaNoS, HRSUNE, BIDASYS, Macau, China, June 16-18, 2014, Revised Selected Papers - Chen, Yueguo; Balke, Wolf-Tilo.; Xu, Jianliang; Xu, Wei.; Jin, Peiquan; Lin, Xin.; Tang, Tiffany; Hwang, Eenjun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of 5 workshops of the 15th International Conference on Web-Age Information Management, WAIM 2014, held in Macau, China, June 16-18, 2014. The 38 revised full papers are organized in topical sections on the six following workshops: Second International Workshop on Emergency Management in Big Data Age (BigEM 2014), Second International Workshop on Big Data Management on Emerging Hardware (HardBD 2014), International Workshop on Data Management for Next-Generation Location-based Services (DaNoS 2014), International Workshop on Human Aspects of Making Recommendations in Social Ubiquitous Networking Environment (HRSUME 2014), International Workshop on Big Data Systems and Services (BIDASYS 2014).
International Workshop on Emergency Management in Big Data Age (BigEM 2014) -- International Workshop on Big Data Management on Emerging Hardware (HardBD 2014) -- International Workshop on Data Management for Next-Generation Location-based Services (DaNoS 2014) -- International Workshop on Human Aspects of Making Recommendations in Social Ubiquitous Networking Environments (HRSUNE 2014) -- International Workshop on Big Data Systems and Services (BIDASYS 2014).
Keywords: Computer science; Computer communication systems; Algorithms; Database management; Data mining; Information storage and retrieval; Computer Science; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Database Management; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Electronic books